RETRACTED: Influence Compensation, Motivation and Work Ethics to Performance Employee Directorate General Right Asasi Man Jakarta South - Nurlaily Dariati; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
Analyzing study following aim To use analyze about influence compensation, motivation And ethics Work to performance employee Directorate General Right Asasi Man. Type study use technique quantitative, method descriptive And method analysis data with use inferential analysis of multiple linear regression and using primary data in the form of a closed questionnaire to 100 respondents assisted by using application SPSS program version 23.0. As there is influence positive as well as from analysis prove that three variable free own influence on variable defenden. From results study This expect company For notice And evaluate Good from performance employee so Can increase more become Good And effective related Which can influence it.